Analisis Faktor-Faktor Yang Mempengaruhi Keputusan Pembelian Impulsif Pada Pengguna Tiktok Shop - Nofian Ubaedilah; Puji Isyanto; Asep Darojatul Romli (Journal of Trends Economics and Accounting Research, 2023)
The phenomenon of "TikTok Temptation" has emerged due to the diverse and captivating content on the platform, such as trending product reviews. Viewers who don't want to miss out often find themselves drawn to products that are going viral and being discussed by content creators. Such content sparks curiosity in many individuals, leading them to frequently make impulsive purchases of these products through TikTok Shop, sometimes even without prior planning. The aim of this research is to uncover the factors influencing impulsive buying decisions. Building on previous studies, impulsive buying decisions are influenced by various factors, including sales promotions, positive emotions, shopping motivation, and price perception. The desired respondents for this study are students of the Faculty of Economics and Business at UBP Karawang from the 2018, 2019, and 2020 cohorts, who use the TikTok app and have made purchases through TikTok Shop. Data was collected through questionnaires distributed to respondents meeting the specified criteria. The data processing technique employed in this research is Partial Least Square (PLS) using the SmartPLS 3 application. The findings indicate that sales promotions, positive emotions, shopping motivation, and price perception have a positive and significant influence on impulsive buying decisions. The impulsive buying decision variable can be explained by sales promotions, positive emotions, shopping motivation, and price perception, accounting for 94.4%, with the remaining variance attributed to other variables.